Glucocorticoids reset circadian clock in choroid plexus via period genes - Liška, Karolína; Sládek, Martin; Čečmanová, Vendula; Sumová, Alena (The Journal of endocrinology, 2021)
The epithelial cells of choroid plexus (CP) in brain ventricles produce cerebrospinal fluid and act as the blood-cerebrospinal fluid barrier. In this study, we confirmed that CP in the 4th ventricle is composed of cellular oscillators that all harbor glucocorticoid receptors and are mutually synchronized to produce a robust clock gene expression rhythm detectable at the tissue level in vivo and in vitro. Animals lacking glucocorticoids (GCs) due to surgical removal of adrenal glands had Per1, Per2, Nr1d1 and Bmal1 clock gene rhythmicity in their CP significantly dampened, whereas subjecting them to daily bouts of synthetic GC analog, dexamethasone (DEX), reinforced those rhythms. We verified these in vivo effects using an in vitro model of organotypic CP explants; depending on the time of its application, DEX significantly increased the amplitude and efficiently reset the phase of the CP clock. The results are the first description of a PRC for a non-neuronal clock in the brain, demonstrating that CP clock shares some properties with the non-neuronal clocks elsewhere in the body. Finally, we found that DEX exhibited multiple synergic effects on the CP clock, including acute activation of Per1 expression and change of PER2 protein turnover rate. The DEX-induced shifts of the CP clock were partially mediated via PKA-ERK1/2 pathway. The results provide the first evidence that the GC rhythm strengthens and entrains the clock in the CP helping thus fine-tune the brain environment according to time of day.
Keywords: cirkadiánní proteiny Period; Circadian Clocks; dexamethason; Male; Rats, Wistar; plexus chorioideus; circadian clock; Choroid Plexus; Dexamethasone; mužské pohlaví; Suprachiasmatic Nucleus; potkani Wistar; MAP kinasový signální systém; Glucocorticoids; krysa rodu Rattus; phase–response curve; MAP Kinase Signaling System; circadian entrainment; Animals; choroid plexus; glukokortikoidy; nucleus suprachiasmaticus; Adrenal Glands; Period Circadian Proteins; zvířata; Rats; dexamethasone; nadledviny; glucocorticoids; cirkadiánní hodiny